IMPLANTATION OF A PERMANENT PACEMAKER IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - V. V. Plechev; I. A. Nagaev; I. M. Karamova; M. V. Nazarov; I. Sh. Sagitov; I. E. Nikolaeva (Креативная хирургия и онкология, 2017)
The article  presents a retrospective analysis  of  patients admitted to  the  Republican out-patient clinic of cardiology   with a diagnosis of acute  myocardial  infarction, no later than  4 hours  from  the  time  of  occurrence  of  symptoms  of  acute  coronary  syndrome. The relationship infarct related  artery  with the development of atrioventricular conduction disturbances in patients undergoing stenting and / or balloon angioplasty of the coronary arteries. A group of  patients with persistent atrioventricular conduction disturbances that took place  in the future  implantation of a permanent pacemaker.